Influence of Sodium and Calcium on Vegetation at Saline Desert (Little Rann of Kutch) of Gujarat State in India - Pilania, P K; Panchal, N S (Annals of Arid Zone, 2016)
Scrutiny of soil and vegetation with their inter-relationship can effectively assist in recognition of the factors to combat land degradation. Saline desert (Little Rann of Kutch of 8820 ha) was selected, for the study of soil (physical and chemical properties) and vegetation. Species richness for herbs was 12, 46, 9, 13 and 35 at Site 1 to 5. Highest density of herbs (21.967 plants m-2) with high FC, OC, OM, N, P and Ca (31.400, 0.799, 1.377, 0.069%, 63.202 kg ha-1 and 194.218 mg kg-1) and low BD, EC, K, Na and Pb at Site 5. Lowest density for herbs (2.208 plants m-2) was found with high values of PD, EC, Na and Pb (2.861 gcc-1, 14.581 dS m-1, 137.310 and 67.309 mg kg-1) and low values of OC, N, Ca and Fe at Site 3. Density of shrubs/trees was highest (8.519 plants 10 m-2) at Site 2 with high values of OC, N, Ca and Mn and low values of EC, Na and Pb. Density has negative correlation with Na, EC and clay while positive with OC and Ca. Low species richness and density is the result of low concentration of OC, OM, N, P, Fe, Ca and high concentration of clay, Na, Pb and EC